Identification of secreted phosphoprotein 1 gene as a new rheumatoid arthritis susceptibility gene. Issue 3 (21st January 2014) - Gazal, Steven; Sacre, Karim; Allanore, Yannick; Teruel, Maria; Goodall, Alison H; ,; Tohma, Shigeto; Alfredsson, Lars; Okada, Yukinori; Xie, Gang; Constantin, Arnaud; Balsa, Alejandro; et al.
Abstract : Objective: To evaluate the contribution of the SPP1 rs11439060 and rs9138 polymorphisms, previously reported as autoimmune risk variants, in the rheumatoid arthritis (RA) genetic background according to anti-citrullinated protein antibodies (ACPAs) status of RA individuals. Methods: We analysed a total of 11 715 RA cases and 26 493 controls from nine independent cohorts; all individuals were genotyped or had imputed genotypes for SPP1 rs11439060 and rs9138. The effect of the SPP1 rs11439060 and rs9138 risk-allele combination on osteopontin (OPN) expression in macrophages and OPN serum levels was investigated. Results: We provide evidence for a distinct contribution of SPP1 to RA susceptibility according to ACPA status: the combination of ≥3 SPP1 rs11439060 and rs9138 common alleles was associated mainly with ACPA negativity (p=1.29×10 −5, ORACPA-negative 1.257 (1.135 to 1.394)) and less with ACPA positivity (p=0.0148, ORACPA-positive 1.072 (1.014 to 1.134)). The ORs between these subgroups (ie, ACPA-positive and ACPA-negative) significantly differed (p=7.33×10 −3 ). Expression quantitative trait locus analysis revealed an association of the SPP1 risk-allele combination with decreased SPP1 expression in peripheral macrophages from 599 individuals. To corroborate these findings, we found an association of the SPP1 risk-allele combination and low serum level of secreted OPN (p=0.0157), as well as serum level of secreted OPN correlated positively with ACPA production (p=0.005; r=0.483). Conclusions: We demonstrate a significant contribution of the combination of SPP1 rs11439060 and rs9138 frequent alleles to risk of RA, the magnitude of the association being greater in patients negative for ACPAs.